Bacillus subtilis and Bacillus megaterium in the initial growth of 'Sugar Baby' watermelon (Research, Society and Development, 2022)
Given the need to reduce production costs and make pesticide-free products available in the watermelon supply chain, the objective of this study was to evaluate the influence of bacteria of the genus Bacillus subtilis and Bacillus megaterium on germination and biometry of watermelon seeds and seedlings. cv. Sugar Baby. The research was carried out at the Centro de Ciências de Chapadinha, of the Universidade Federal do Maranhão (CCCh/UFMA). The study was carried out in a completely randomized experimental design in a 5x3 factorial scheme (five immersion times (0, 6, 12, 18 and 24 hours) x three bioinputs (B. subtilis; B. megaterium and the co-inoculation of B. subtilis + B. megaterium)) with 40 replications. Data were submitted to ANOVA and means were compared by the Duncan test (P